A pilot study on quantification of training load: The use of HRV in training practice. Issue 2 (17th February 2016) - Saboul, Damien; Balducci, Pascal; Millet, Grégoire; Pialoux, Vincent; Hautier, Christophe
Abstract: Recent laboratory studies have suggested that heart rate variability (HRV) may be an appropriate criterion for training load (TL) quantification. The aim of this study was to validate a novel HRV index that may be used to assess TL in field conditions. Eleven well-trained long-distance male runners performed four exercises of different duration and intensity. TL was evaluated using Foster and Banister methods. In addition, HRV measurements were performed 5 minutes before exercise and 5 and 30 minutes after exercise. We calculated HRV index (TLHRV ) based on the ratio between HRV decrease during exercise and HRV increase during recovery. HRV decrease during exercise was strongly correlated with exercise intensity ( R = −0.70; p < 0.01) but not with exercise duration or training volume. TLHRV index was correlated with Foster ( R = 0.61; p = 0.01) and Banister ( R = 0.57; p = 0.01) methods. This study confirms that HRV changes during exercise and recovery phase are affected by both intensity and physiological impact of the exercise. Since the TLHRV formula takes into account the disturbance and the return to homeostatic balance induced by exercise, this new method provides an objective and rational TL index. However, some simplification of the protocol measurement could be envisaged for field use.